Factorial Modeling of Energy Requirements of Japanese Quail in the Starter and Grower Phases (Research, Society and Development, 2020)
This study quantified the apparent metabolizable energy (ME) requirements for maintenance and gain in female Japanese quail (1-35 d of age) using a factorial approach combined with the comparative slaughter technique. A total of 655 quail were evaluated across two phases: starter (1-14 d) and grower (15-35 d). For maintenance, caged quail were offered 100, 75, 50, or 25% of ad libitum intake; for gain, reference and sequential serial slaughters were conducted. Recorded variables included feed intake, ME intake (MEi), fasted carcass weight (FCW), carcass energy (CE), energy in carcass dry matter (EDM), retained energy (RE), and heat production (HP). The ME requirement for maintenance (MEm) was estimated by linear regressions of RE on MEi and expressed per metabolic body weight (BW0.67); net energy for maintenance (NEm) was derived from regressions of HP on MEi. In the starter phase, MEm = 54.96 kcal.kg-0.67.d-1 and the efficiency of ME use for gain (k) was 16.92%; in the grower phase, MEm = 92.11 kcal.kg-0.67.d-1 and k = 21.27%. NEm was 53.27 and 57.88 kcal.kg-0.67.d-1 for starter and grower, yielding maintenance efficiencies (km = NEm/MEm) of 96.93% and 62.84%. Net energy for gain (NEg) was 1.40 and 1.896 kcal.g-1.d-1. resulting in dietary requirements for weight gain of 8.30 and 8.91 kcal.g-1.d-1, respectively. The prediction equations were Starter - ME (kcal.quail-1.d-1) = 54.96 × BW0.67 + 8.30 × WG; Grower - ME (kcal.quail-1.d-1) = 92.11 × BW0.67 + 8.91 × WG; where BW is live body weight (kg) and WG is daily weight gain (g.quail-1.d-1). Mean ambient temperature was 24.05°C (max 35.2°C), suggesting environmental effects on maintenance requirements.